2016
DOI: 10.3390/ijms17121999
|View full text |Cite
|
Sign up to set email alerts
|

Coriandrum sativum and Lavandula angustifolia Essential Oils: Chemical Composition and Activity on Central Nervous System

Abstract: The aims of this study are to determine the chemical composition of Lavandula angustifolia Mill. and Coriandrum sativum L. essential oils, to evaluate their cytotoxic effects in SH-SY5Y human neuroblastoma cells, to investigate whether an alteration of adenylate cyclase 1 (ADCY1) and of extracellular signal-regulated kinase (ERK) expression can take part in the molecular mechanisms of the essential oils, and to study their possible neuronal electrophysiological effects. The essential oils were obtained by hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
(51 reference statements)
3
36
1
3
Order By: Relevance
“…Elisabetsky and coworkers showed that linalool possesses dose-dependent sedative effects in the Central Nervous System [33]. In our previous study, we reported that linalool is a component of many essential oils that can influence the expression of ADCY1 and ERK [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Elisabetsky and coworkers showed that linalool possesses dose-dependent sedative effects in the Central Nervous System [33]. In our previous study, we reported that linalool is a component of many essential oils that can influence the expression of ADCY1 and ERK [34]. …”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, essential oil components have been evaluated for their mechanism of action and to obtain leading compounds active in central nervous system (CNS). Linalool alone as well as the L. angustifolia essential oils affect, in a concentration‐dependent manner, neural firing activity . L. angustifolia EO exerts receptor binding affinities with a relevant activity on the N ‐methyl‐ d ‐aspartate receptor and inhibition of the serotonin transporter .…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Linalool alone as well as the L. angustifolia essential oils affect, in a concentrationdependent manner, neural firing activity. [366] L. angustifolia EO exerts receptor binding affinities with a relevant activity on the N-methyl-D-aspartate receptor and inhibition of the serotonin transporter. [367] Inhalation and the external application of these oils for the treatment of mental and physical balance are the very basics of aromatherapy in which olfactory nerves from nose to the brain are the site of action for these essential oils.…”
Section: Eos and Human Healthmentioning
confidence: 99%
“…Linalool also shows antidepressant-like effects, decreasing immobility time in the tail suspension test [ 21 ]. In our previous studies, we reported that Lavandula angustifolia , Coriandrum sativum , and Laurus nobilis essential oils and their main components, i.e., linalool and 1,8-cineole, influenced adenylate cyclase 1 (ADCY1) expression [ 22 , 23 ]. ADCY1 possesses a crucial role in the CNS; in fact, synaptic plasticity and memory formation depend on optimal cAMP levels.…”
Section: Introductionmentioning
confidence: 99%